The Role of Transformational Leadership Style in Mediating Work Stress and Work Motivation on Employee Performance - Lela Nurlela Fitriani; Triyuni Soemartono; Jubery Marwan (PT. Mega Mas Abadi Konsultan, 2025)
The objective of this research is to investigate the role that transformational leadership plays in mediating the relationship between employee performance and the degree to which stress and motivation at work are affecting employees. This research was carried out in the Baros District of the Serang Regency, and it utilized a quantitative methodology from the beginning. The primary data were acquired through the use of purposive sampling, and then they were analyzed through the use of Path Analysis. These data were tested for reliability, validity, and normalcy. Despite the fact that work motivation has a beneficial affect on both transformational leadership and employee performance, the data indicate that stress at work does not have a substantial impact on transformational leadership. Additionally, in contrast to job motivation, stress at work does not have a direct influence on employee performance. Moreover, the research draws attention to the fact that transformational leadership has an effect on employee performance, but stress at work does not have this effect. High workloads, pressure from leadership, dangerous duties, role conflicts, insufficient organizational support, and a lack of motivation and effective leadership are all factors that can be related to the deterioration in employee performance. Leaders are responsible for effectively guiding and influencing their subordinates, pushing them to attain their full potential, and providing an example for others to follow.